Differential evolution based parameter identification of static and dynamic J-A models and its application to inrush current study in power converters - Huang, Song. (2013)
The Jiles-Atherton (J-A) model is very suitable for modeling ferrite-core based inductors and transformers. In this paper the differential evolution (DE) method was applied to extract five parameters in static J-A model first. Then it was applied to extract another two parameters in dynamic J-A model with five parameters in static J-A model as inputs. It is found that extracting five parameters in static J-A model is relatively easy but extracting another two parameters in dynamic J-A model needs extra effort, especially specifying their ranges. After obtaining all seven parameters, we applied dynamic J-A model to predict the current behavior of a practical switching circuit and successfully obtained the inrush current phenomenon as experimentally observed and reported in literature. We conclude that application of DE method to extract seven parameters in dynamic J-A model for ferrite is feasible.